Experimental Investigations into Sarcomas Therapy Using Ferromagnetically Induced Cytostatics - Krukemeyer, Manfred Georg (Springer Fachmedien Wiesbaden, 2018)
Manfred Georg Krukemeyer first describes magnetic drug targeting, by which is meant the focused application of drugs, e.g. the introduction of a cytostatic, and which is aimed at optimising its locally therapeutic effect. The author thus achieves a high concentration of cytostatic at the site of the tumour. The particles have to be large enough to be attracted by a magnetic field and so find their way into the tumour, where they release their active ingredient. The aim of the hypothesis formed by one of the author's study groups was to show in a scientific experiment that in this case cytostatics coupled with iron particles [Fe3O4] can be introduced into a tumour. The focused introduction of drugs - magnetic drug targeting - results in faster arrival of the active ingredient at the target site together with a reduced quantity of active substances. For this reason magnetic drug targeting is also interesting from an economic point of view. Contents Sarcomas and their Pathology Magnetic Drug Targeting Animal Testing and Patient Examination, Tumour Therapy in Humans Target groups Researchers, teachers and students in surgical and oncology departments Doctors working in the fields of surgery and oncology About the author Dr. med. Manfred Georg Krukemeyer is a specialist surgeon currently holding a senior position at a large German hospital enterprise.